American book prices current. (New York R.R. Bowker, 1894)
Annual
"A record of literary properties sold at auction in the United States."
Vol. 31, 1924/25, includes books only; the record of manuscripts and autographs is included in v. 32; Vols. 22-28, 1915/16-1921/22. 1 v.; Vols. 29-38, 1922/23-1931/32. 1 v.; Vols. 39-46, 1932/33-1939/40. 1 v.; Vols. 47-51, 1940/41-1944/45. 1 v.; Vols. 52-56, 1945/46-1949/50. 1 v.; Vols. 57-61, 1950/51-1954/55. 1 v.; Vols. 62-66, 1955/56-1959/60. 1 v.; Vols. 67-71, 1960/61-1964/65. 1 v.; Vols. 85-89, 1979-1983. 2 v.
Keywords: Books -- Prices -- Periodicals; Autographs -- Prices -- Periodicals; Book auctions -- Catalogs -- Indexes; Manuscripts -- Prices -- Periodicals; Rare books -- Prices -- Periodicals